A Glance into the Status of English Language in the Algerian Higher Education Context - rahmani, asma (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
The present paper is an action research that attempts to investigate the effectiveness of adopting English language in the Algerian university level. Undeniably, the English language is perceived as a significant tool to possess an international understanding of the different life issues and world’s various regulations. To gain empirical data, an online questionnaire was administered to a sample of 89 teachers of different subjects at three distinct faculties: Social and Human Science, languages, and Science and Technology at 20 Algerian universities. The selection of the sample was based first on the simple random selection and then on the non- probability linear snowball technique. Notably, the questionnaire aims at revealing the participants’ viewpoints, perceptions and expectations of embracing English as a formal language. The analyses of the obtained data reveal that the university teachers believe that the endorsement of English in education will promote the learning process and its quality. Ultimately, this paper elucidates some recommendations to facilitate such endorsement and make it more beneficial.